Strategic Industrial Policies When Firm Has Bargaining Power - Carlo Scarpa (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1990)
This paper studies the optimal behavior of a regulator facing tho markets monopolized by two firms: one of them has bargaining power, while the other can be foced to accept any regulatory constraint, and can be thus treated as a public firm. the interaction between the strategic choices of the public firm and the regulation of the other one is analyzed. It is shown that regulating prices is better than regulating output levels, and that the optimal strategy is to fix the price of the public firm befor bargaining with the private one. This suggests also an argument in favour of centralizing regulation, instead of having separate regulatory bodies.
Keywords: 330